PENGARUH EMBUNG DAN KOMBINASINYA DENGAN TEKNIK KONSERVASI TANAH DAN AIR LAINNYA TERHADAP KOEFISIEN REGIM ALIRAN DAN KOEFISIEN ALIRAN TAHUNAN - Rahman, Latief M; Nursari, Evi; Baskoro, Dwi Putro Tejo (UI Scholars Hub, 2018)
Government of Indonesia planned to build 30.000 embung in 2017. Embung or mini reservoir is one of soil and water conservation methods to decrease surface runoff, enhance water surface retention, and increase water entering to the soil by infiltration, that finally influence the values of Discharge Ratio and Runoff Coefficient of a watershed. This research that was done in 2017 is about the effect of embung and it’s combination with other soil and water conservation technics (strip cropping and agroforestry) on Discharge Ratio (DR) and Runoff Coefficient (RC) in Cilemer Watershed by using SWAT method. The result shows that the Scenario 1 (mini reservoir technic alone) decreased DR and RC by 25.45% (from 119.70 to 94.25) and 32% (from 0.25 to 0.17), respectively. The Scenario 2 (combination of embung and strip cropping) decreased DR and Runoff Coefficient by 40.92% (from 119.70 to 78.78) and 32% (from 0.25 to 0.17), respectively. The Scenario 3 (combination of mini reservoir and agroforestry) decreased DR and RC by 41.38% (from 119.70 to 78.31) and 36% (from 0.25 to 0.16), respectively. The application of mini reservoir and its combination with other soil and water conservation (SWC) techniques were able to decrease DR and RC meaningfully.